Analisis Tipologi Keterkaitan Interaksi Desa Kota dengan Kemiskinan di Kecamatan Kokap, Kabupaten Kulon Progo - Kharisma Octaviana Putri Anjani; Samsul Ma'rif (Teknik PWK (Perencanaan Wilayah Kota), 2020)
Rural and urban should be seen as unity in regional development. One of the issue from regional development is poverty and rural urban linkages can be the strategy to reduce poverty. Kokap Sub-district divided into five villages such as Hargowilis, Hargorejo, Hargotirto, Kalirejo, and Hargomulyo is the poorest sub-district in Kulon Progo Regency and located in the hills, which makes Kokap Sub-district being isolated. The purpose of this study is to examine how the typology between the level of poverty and rural urban interaction in Kokap Sub-district is. The analytical methods are using statistic descriptive, quantitative descriptive, scoring and typology. The level of poverty divided into two categories, low level of poverty and high level of poverty, then the level of rural urban interaction also divided into two categories, which are strong level of linkages and weak level of linkages. The results of the analysis shown that Hargowilis including to low level of poverty and strong level of linkages, Hargomulyo including to low level of poverty and high level of linkages, and Hargorejo, Hargotirto, and also Kalirejo including to high level of poverty and weak level of linkages.